Analysis of Liability Models in the Juvenile Justice Drama Series from a Criminal Law Perspective - Prayudi; Purwanda, Sunardi; Sabir, Muhammad; Tijjang, Bakhtiar; Mannan, Khaerul (Institut Agama Islam Negeri Kendari, 2025)
Juvenile crime constitutes a complex legal phenomenon that cannot be separated from the influence of the social environment, particularly the involvement of adults surrounding the child. The television drama Juvenile Justice portrays juvenile crime not merely as an individual act, but as the result of power relations, neglect, and exploitation by adults who bear legal duties of supervision and protection. This study aims to analyze patterns of adult involvement in juvenile crime and to assess the relevance of the doctrine of vicarious liability from a criminal law perspective. Employing normative legal research with a qualitative approach, this study applies both conceptual and case-based approaches. The data were derived from primary and secondary legal materials, complemented by scene analysis of Juvenile Justice as an object of popular culture studies. The findings indicate that juvenile अपराध in the series is structurally connected to the role of adults, either through failures of supervision or through active involvement that facilitates the commission of criminal acts. The doctrine of vicarious liability is therefore considered relevant as a legal instrument for extending criminal responsibility to adult actors who make significant contributions to juvenile crime, without undermining the principles of legality and culpability. This study concludes that the application of vicarious liability may serve as a more just and proportionate alternative within the juvenile criminal justice system by allocating criminal responsibility in a balanced manner between child offenders and the adult actors operating behind the commission of the crime.